2017
DOI: 10.4314/njt.v36i2.31
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of an electric power distribution network planning system using mixed binary integer programming

Abstract: In this paper, the electric distribution network expansion planning problem (EDNEPP) was solved by a mixed binary integer programming (MBIP) formulation of the network, where the steady-state operation of the network was modelled with non-linear mathematical expressions. The non-linear terms are linearized, using piecewise linearization of the nonlinear expressions, so as to ensure the model computational compatibility with existing commercial optimization solvers. The linearized formulation is verified to ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
0
0
2
Order By: Relevance
“…The main problem here is to take into account as complete a set of information as possible about the oil and gas production facilities in operation, from the required capacity for energy consumers to the properties of the produced hydrocarbons. There are many different tools and methods aimed at its solution [31,37,38]. In our previous study [39], the authors identified the current global trends of electrification and power supply and identified the specifics of using modern technologies for the electrification of hydrocarbon production facilities in poorly developed or hard-to-reach territories of Russia.…”
Section: An Overview Of Modern Technologies For the Electrification O...mentioning
confidence: 99%
“…The main problem here is to take into account as complete a set of information as possible about the oil and gas production facilities in operation, from the required capacity for energy consumers to the properties of the produced hydrocarbons. There are many different tools and methods aimed at its solution [31,37,38]. In our previous study [39], the authors identified the current global trends of electrification and power supply and identified the specifics of using modern technologies for the electrification of hydrocarbon production facilities in poorly developed or hard-to-reach territories of Russia.…”
Section: An Overview Of Modern Technologies For the Electrification O...mentioning
confidence: 99%
“…3. Модернизация системы электроснабжения [12][13][14][15]. Авторами [12] предложен комплексный подход к модернизации системы электроснабжения.…”
unclassified
“…Модернизация системы электроснабжения [12][13][14][15]. Авторами [12] предложен комплексный подход к модернизации системы электроснабжения. Алгоритм позволяет определить целесообразность замены оборудования при недостаточной пропускной способности, оценить издержки в результате перебоев электроснабжения, а также в случае необходимости замены оборудования определить характеристики и место установки.…”
unclassified